Magnetic Actuation Systems for Miniature Robots: A Review. (24th June 2020) - Yang, Zhengxin; Zhang, Li
Abstract : A magnetic field, which is transparent and relatively safe to biological tissue, is a powerful tool for remote actuation and wireless control of magnetic devices. Furthermore, miniature robots can access complex and narrow regions of the human body as well as manipulate down to subcellular entities; however, integrating onboard components is difficult due to their limited size. Combining these two technologies, magnetic miniature robots have undergone rapid development during the past two decades, mainly because of their high potential in medical and bioengineering applications. To improve the scientific and clinical outcomes of these tiny agents, developing suitable and reliable actuation systems is essential. As a newly emerging field that has progressed in recent years, magnetic actuation systems offer a harmless and effective approach for the remote control of miniature robots via a dynamic magnetic field. Herein, a review on the state‐of‐the‐art magnetic actuation systems for miniature robots is presented with the goal of providing readers with a better understanding of magnetic actuation and guidance for future system design. Abstract : Magnetic miniature robots have shown potential in medical and bioengineering applications. To improve their scientific and clinical outcomes, developing suitable and reliable actuation systems is essential. Herein, a review on the state‐of‐the‐art magnetic actuation systems for miniature robots is presented with the goal of providing readers a better understanding of magnetic actuation and guidance for future system design.